Kondisi Geologi Teknik Daerah Jalur Jalan Cangakan-Sidoladju Kabupaten Ngawi Propinsi Jawa Timur (Studi Kasus : Instabilitas Jalan dan Cara Mengatasinya) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
This research is purposed to know the condition of geological engineering along Cangakan Sidoladju road and to study the character of expansive clay as a subgrade of the road that causes road instability. Based on field observation and laboratory work, there are 3 geomorphological units in research area, e.g. a fluvial plain unit, aluvial plain unit, and undulating slope denudational unit. The stratigraphic of the area consists of 6 units, namely marl, limestone , sandstone, breccia, gravel - sand and clay unit. The geological structure which is found, i.e. Gandong dextral strike slip fault. The geological engineering unit of along the road Cangakan - Sidoladju consists of 3 units : black grey/brow clay unit, grey clay unit, dan clay - silt unit. The damaged road was generally resulted from the expansive subgrade of body road in the form of grey-black clay by high plasticity, which has the number of plastic limit (FL) = 60-100, water content (34 -48)%, shrinkage limit (SL) 10 - 16, and clay fraction about (27 - 50)%. The changes of water content which is influenced by rainfall and land used as rice field needs much water, and also the channel of road drainage that did not work properly causes road damage, i.e. crack along the road, undulating of the upper surface, sagging and also sliding in the shoulder of the road.